KEMAMPUAN PEMECAHAN MASALAH SEGI EMPAT SISWA KELAS VII SMP - Rabiatul Adawiyah; Ayu Veranita; Haeriah Haeriah; Aria Joko Pramono (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2021)
Problem solving ability and understanding of concepts have a very close relationship in problem solving. Understanding the concept becomes an important capital in improving problem solving abilities. This study aims to determine how students' problem-solving skills are based on the level of understanding of students' mathematical concepts in solving quadrilateral story problems. The method used is a descriptive method with a qualitative approach, in the form of student work in working on rectangular questions and followed by in-depth interviews. The research subjects were seventh grade students of SMPN 3 Sampit in the even semester of the 2021/2022 academic year who had different levels of conceptual understanding. This study describes 6 subjects to explore problem solving abilities. The results showed that students with high conceptual understanding were able to understand the problem well by mentioning what was known and what was asked in the problem by writing down a floor area of 6 m × 6 m and a tile area of 40 cm × 40 cm, able to plan a solution well. This is shown from how the subject determines what method/formula/method is used to solve the rectangular problem by writing down the number of tiles needed is the floor area the area of the tile and is able to carry out solving the problems that have been given, but does not re-examine the answers. Meanwhile, students with moderate understanding of the concept are able to understand the problem well, make plans for solving them correctly and carry out the solutions they have made. In addition, students also review the results of their answers and make conclusions on the results of their answers. In this study, students with a moderate understanding of the concept had fulfilled all the indicators of problem solving and were precise in performing calculations. Meanwhile, students with low conceptual understanding are still unable to understand the problem well, have not been able to plan a solution, have not been able to carry out the completion and have not re-examined.